Extrusion-based 3D bioprinting of the cornea using decellularized extracellular matrix - Mohamed Fayaz Bin Nazurudeen (Nanyang Technological University, 2024)
Corena 3D bioprinting represents a revolutionary approach in the realm of ocular health which offers innovative solutions to address the challenges associated with corneal injuries and diseases. The cornea, a vital transparent dome-shaped membrane covering the front portion of the eye plays a crucial role in focusing light onto the retina, maintaining the eye’s shape, and protecting the inner structures of the eye. Despite its significance, corneas are susceptible to injuries which leads to exploration of various treatments such as corneal transplants and Keratoprosthesis. However, challenges like immune rejection and shortage of healthy donor tissues hinder the success of these treatments. This paper proposes a promising alternative through 3D bioprinting, a transformative method capable of engineering artificial corneal structures to substitute donor tissues and expedite wound healing. The utilization of bioinks which are derived from human extracellular matrix introduces a novel avenue for creating artificial corneas that mimic the natural tissue’s composition. Various 3D bioprinting technologies such as Stereolithography (SLA), Digital Light Processing (DLP) and Extrusion bioprinting are discussed in the context of their application to corneal bioprinting. It also highlights the significance of bioink properties, emphasizing the need to adjust concentrations and biomaterials to achieve optimal viscosity and structural stability. Additionally, the establishment of an effective crosslinking method is explored to ensure the durability of the resulting hydrogels. Unlike traditional treatments such as corneal transplants or Keratoprosthesis, 3D bioprinted corneas have the potential to trigger the full recovery of the diseased cornea, offering a comprehensive solution for patients. This project endeavors to contribute to the evolving field of cornea 3D bioprinting by addressing current limitations and proposing avenues for further research. The exploration of advanced techniques and bioink formulations provide a promising trajectory for the development of effective and biocompatible solutions in corneal tissue engineering.